The Impact of Business Process Systematization on the Stability of Beauty Projects During Periods of Economic Uncertainty - Pereshliuga, Kseniia (Global Prosperity, 2023)
Abstract. Economic crises are killing beauty salons at an alarming rate. People drastically reduce spending on "non-essentials", and trips to the salon are the first to be cut. But the strange thing is that some salons close in six months, others somehow live the same conditions and even come out stronger. The secret is not in the location, not in the prices, not even in the skill of the staff. The secret is whether there are systems in the cabin or whether everything rests on the intuition of the owner and the knowledge of a few key people. This article analyzes how the systematization of business processes determines who will survive the crisis and who will not. We consider why beauty salons are especially vulnerable during economic storms, how systematization creates stability through financial transparency, documented processes, a normal client base, and quality standards. But we also honestly talk about the dark side - when excessive systematization kills liveliness and turns the salon into a soulless conveyor belt. The key is in the balance: systematize finances, customer base, inventory, basic standards, but leave room for creativity, human communication, flexible solutions. We show how to start systematizing in small steps without crazy budgets and why the crisis is paradoxically the best time for this. The main conclusion is simple: in conditions of constant instability, systematization is not a luxury, but a basic infrastructure of survival.